Amperometric immunosensor based on the conducting layer of PAni/Fe3 O4 nanocomposites for the detection of Aβ42 (Journal of Pure and Applied Sciences (Science Forum), 2026)
Conducting PAni/Fe3O4 nanocomposites were synthesized and electrochemically deposited on fluorine-tin-oxide (FTO)-coated glass to form a transducing layer owing to their catalytic, magnetic, and electrical properties. This synthesized conducting layer was used to immobilized anti-β42 for the detection of Alzheimer’s disease. The electrode modification process was characterized by electrochemical impedance spectroscopy, cyclic voltammetry, and field emission scanning electron microscopy. Some factors influencing the performance of the amperometric immunosensor were optimized. The experiment outcome indicates a conducting layer of the nanocomposites on the FTO-coated glass in the range of −1.5 to 0.5 V at 0.10 Vs−1 in a 10 ml solution of PAni-Fe3O4 nanocomposites. Electrochemical impedance changes occurred only after PAni/Fe3O4 bound to surface of bare FTO, confirming the deposition and indicating that the new modified electrode can be used as a transducing matrix for the immobilization of the biomarker. Tests performed with this immunosensor showed good linearity with a detection limit of 0.061 µg/ml−1 at 3σ.